Thermomechanically micronized sugar beet pulp: Emulsification performance and the contribution of soluble elements and insoluble fibrous particles. (March 2023) - Lin, Jiawei; Tang, Zhong-Sheng; Brennan, Charles S.; Chandrapala, Jayani; Gao, Wenhong; Han, Zhong; Zeng, Xin-An
Graphical abstract: Highlights: Thermomechanically micronized sugar beet pulp has soluble and insoluble fractions. Microfludization was efficient to fabricate smaller and more stable emulsions. Fibrous particles tangled as a network to warp droplets as a flocculated state. Gel-like properties of MSBP emulsions enhanced after storage. Hybrid coverage of soluble and insoluble fractions co-stabilized the emulsion. Abstract: In this work, thermomechanically micronized sugar beet pulp (MSBP), a micron-scaled plant-based byproduct comprised of soluble elements (∼40 wt%) and insoluble fibrous particles (IFPs, ∼60 wt%), was used as a sole stabilizer for oil-in-water emulsion fabrication. The influence of emulsification parameters on the emulsifying properties of MSBP was investigated, including emulsification techniques, MSBP concentration, and oil weight fraction. High-speed shearing (M1), ultrasonication (M2), and microfludization (M3) were used to fabricate oil-in-water emulsions (20% oil) with 0.60 wt% MSBP as stabilizer, in which the d 4, 3 value was 68.3, 31.5, and 18.2 μm, respectively. Emulsions fabricated by M2 and M3 (higher energy input) were more stable than M1 (lower energy input) during long-term storage (30 days) as no significant increase of d 4, 3 . As compared to M1, the adsorption ratio of IFPs and protein was increased from ∼0.46 and ∼0.34 to ∼0.88 and ∼0.55 by M3. Fabricated by M3, the creaming behavior of emulsions was completely inhibited with 1.00 wt% MSBP (20% oil) and 40% oil (0.60 wt% MSBP), showing a flocculated state and could be disturbed by sodium dodecyl sulfate. The gel-like network formed by IFPs could be strengthened after storage as both viscosity and module were significantly increased. During emulsification, the co-stabilization effect of the soluble elements and IFPs enabled a compact and hybrid coverage onto the droplet surface, which acted as a physical barrier to endow the emulsion with robust steric repulsion. Altogether, these findings suggested the feasibility of using plant-based byproducts as oil-in-water emulsion stabilizers.